Exigências de fósforo disponível para suínos selecionados geneticamente para deposição de carne em diferentes fases de crescimento, dos 15 aos 120 kg - Claudio Luiz Correa Arouca (2008)
Four experiments were conducted in order to determine available phosphorus requirements for swine selected to lean deposition in different growth phases, for 15 to 120 kg. In the experiments were used a randomized complete block design. From 15 to 30 kg, were used 60 barrows and gilts, with 6 treatments, 5 replicates and 2 pigs per pen. Were observed quadratic effect of AP on ADG, DFI, FC, AP-21, P-21 and BS-Front. There was linear effect on DPI, and BS-Rear. It was concluded that high lean barrows and gilts require .57 % of AP, from 15 to 30 kg. From 30 to 60 kg, were used 60 barrows with 5 treatments, 6 replicates and 2 pigs per pen. Were observed quadratic effect of AP on ADG, DFI, FC, P-21 and P-Final. There was linear effect on DPI, AP-21 and AP-Final. It was concluded that high lean barrows require .39 % of AP, from 30 to 60 kg. From 60 to 95 kg, were used 60 barrows, with 5 treatments, 6 replicates and 2 pigs per pen. Were observed quadratic effect of AP on ADG, FC, AP-Final, P-21, P-Final, LD, DLG and LGA. There was linear effect on DPI, and AP-21. There was no effect on DFI, BT-P1, BT-P2, LP, CY, BT-Slaught, LD-Slaught and LP-Slaught. It was concluded that high lean barrows require .33 % of AP, from 60 to 95 kg. From 95 to 120 kg, were used 80 barrows, with 5 treatments, 8 replicates and 2 pigs per pen. Were observed quadratic effect of AP on ADG, FC, AP-21, P-21. There was linear effect on DPI. There was no effect on DFI, BT-P1, BT-P2, LD, LP, DLG, CY, BT-Slaught, LD-Slaught, LGA and LP-Slaught.. It was concluded that high lean barrows require .20 % of AP, from 95 to 120 kg.